Treatment of Pulpectomized Teeth With Trypsin Prior to Transplantation of Mobilized Dental Pulp Stem Cells Enhances Pulp Regeneration in Aged Dogs - Iohara, Koichiro; Zayed, Mohammed; Takei, Yoshifumi; Watanabe, Hideto; Nakashima, Misako (Frontiers in Bioengineering and Biotechnology, 2020)
There is an age-dependent decline of pulp regeneration, due to the decline of migration, proliferation, and cell survival of resident stem cells. Trypsin is a proteolytic enzyme clinically used for tissue repair. Here, we investigated the effects of trypsin pretreatment of pulpectomized teeth prior to cell transplantation on pulp regeneration in aged dogs. The amount of regenerated pulp was significantly higher in trypsin-pretreated teeth compared to untreated teeth. Trypsin pretreatment increased the number of cells attached to the dentinal wall that differentiated into odontoblast-like cells. The trypsin receptor, PAR2, was higher in vitro expression in the periodontal ligament cells (PDLCs) from aged dogs compared to those from young. The direct effects of trypsin on aged PDLCs were increased expression of genes related to immunomodulation, cell survival, and extracellular matrix degradation. To examine the indirect effects on microenvironment, highly extracted proteins from aged cementum were identified by proteomic analyses. Western blotting demonstrated that significantly increased fibronectin was released by the trypsin treatment of aged cementum compared to young cementum. The aged cementum and dentin extracts by trypsin treatment increased angiogenesis, neurite extension and migration activities as elicited by fibronectin. Furthermore, the dentin extracts significantly increased the mRNA expression of immunomodulatory factors and pulp markers in the aged DPSCs. These results demonstrated the effects of trypsin on the microenvironment in addition to the resident cells including PDLCs in the aged teeth. In conclusion, the potential utility of trypsin pretreatment to stimulate pulp regeneration in aged teeth and the underlying mechanisms were demonstrated.